2018
DOI: 10.1007/s10086-017-1693-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pretreated wood dowel with CuCl2 on temperature distribution of wood dowel rotation welding

Abstract: This study examined the temperature distribution during rotation welding process using birch (Betula spp.) wood dowel and Chinese larch (Larix gmelinii) substrates. Wood dowels were divided into two categories including an untreated group and a group pretreated with cupric chloride. The mechanics test results indicated that the pullout resistance of the pretreated group with welded time 3 s showed the best performance. As a fitting analyses result, both the untreated group and pretreated group showed a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The test results also showed that the treated samples had more melt compared to untreated ones. Dowels treated with CuCl2 with the welding duration of 3 s achieved 68% greater pull-out force than untreated dowels with the same welding time (Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The test results also showed that the treated samples had more melt compared to untreated ones. Dowels treated with CuCl2 with the welding duration of 3 s achieved 68% greater pull-out force than untreated dowels with the same welding time (Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 91%
“…In vibration welding, the strength of the welded joint is twice that of unmodified wood (Boonstra et al 2006). Zhang et al (2018) investigated the impact of treating the birch wood (Betula pendula Roth) dowels with CuCl2 solution on welding temperature and pull-out force. Birch dowels were welded into the base of Chinese larch (Larix gmelinii Rupr.).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the rotational frequency of the dowel also affected a slight increase in temperature during welding and embedded force. Samples that were treated with CuCl2 with a welding process duration of 3 s achieved 68% higher embedded force than untreated samples with the same welding time (Zhang et al 2018). With extension of the welding time, the embedded force was reduced.…”
Section: Introductionmentioning
confidence: 93%
“…Welding depth affects the welding temperature. At a welding depth of 5 mm, the welding temperature was 350 C and it decreases linearly, so at a depth of 23 mm, the welding temperature was 150 C (Zhang et al 2018). The temperature was measured using six thermocouple sensors with the data collecting device.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these examples had included the use of wood structural components (beams and ties) in the construction field because of their high tensile and flexural strengths [21]. An automated optical method in the detection and measurement of decorative plywood panels [22] and the function of a wood dowel in the rotation welding process, where its effectiveness is still being investigated at this point in time [23].…”
Section: Introductionmentioning
confidence: 99%